2023
DOI: 10.3389/fenrg.2023.1161076
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the bias and uncertainty of SNF decay heat calculations using Polaris and ORIGEN

Abstract: The bias and uncertainty of calculated decay heat from spent nuclear fuel (SNF) are essential for code validation. Also, predicting these quantities is crucial for deriving decay heat safety margins, influencing the design and safety of facilities at the back end of the nuclear fuel cycle. This paper aims to analyze the calculated spent nuclear fuel decay heat biases, uncertainties, and correlations. The calculations are based on the Polaris and ORIGEN codes of the SCALE code system. Stochastically propagated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Energies 2023, 16,7378 where β n inf represents the k inf bias propagated to the criticality calculation through the nuclide concentration for the nuclide (n) from the measurement data of fuel sample j in Equation (17). β inf is the k inf bias resulting from all the calculated nuclide concentration biases in Equation (18).…”
Section: Uncertainty Sampling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Energies 2023, 16,7378 where β n inf represents the k inf bias propagated to the criticality calculation through the nuclide concentration for the nuclide (n) from the measurement data of fuel sample j in Equation (17). β inf is the k inf bias resulting from all the calculated nuclide concentration biases in Equation (18).…”
Section: Uncertainty Sampling Methodsmentioning
confidence: 99%
“…Even with the adoption of a coupled diffusion-depletion calculation process and the comprehensive tracking of the fuel assembly position throughout the cycles, it remains challenging to fully account for the actual depletion process of the fuel assembly in the reactor. Moreover, because the depletion calculation requires the decomposition of the burnup chain and the selection of an effective numerical calculation method to obtain the spent-fuel composition at a specific burnup [15], the approximation introduced by the burnup chain decomposition and the inherent error of the numerical calculation method make it difficult to obtain an accurate nuclear fuel composition for the depletion calculation [16,17]. Hence, when the BUC technique is applied, it is essential to analyze the spent-fuel composition used in the depletion calculation in a reasonable and conservative manner and quantify the nuclide concentration uncertainties in the criticality calculation.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the fission products contribute to the decay heat power mainly in the short storage period (<50 years). As highlighted in [4], the accuracy of the results obtained from analytical and numerical calculations depends on the degree of the accuracy of available data and on the use of appropriate cross-section libraries [5][6][7]. At present, most of the calculations of spent fuel characteristics after in-service operation are performed by means of validated numerical codes such as ORIGEN (Oak Ridge Isotope Generation, developed at ORNL, Oak Ridge, TN, USA) or KORIGEN (FZK, Hannover, Germany).…”
Section: Storage Strategiesmentioning
confidence: 99%
“…Several studies have used such computational models in the past to investigate the uncertainty of SNF, e.g. in Shama et al (2023Shama et al ( , 2022 the biases, uncertainties, and correlations of calculated decay heat from SNF using the Polaris and ORIGEN codes were analyzed, finding that both codes exhibited insignificant biases and similar uncertainties and correlations influenced by fuel assembly (FA) burnup and cooling time. The study also made use of machine learning models and the MOCABA algorithm for predicting biases and verifying results.…”
Section: Introductionmentioning
confidence: 99%